A tutela jurisdicional da criança e do adolescente em face da alienação parental - Costa Velho, Bruna Cristina Gonçalves da (2014)
The present study aims to analyze the judicial measures provided at Law 12.318/2010 as a means to combat parental alienation amid the backdrop of the integral protection doctrine adopted by the brazilian Constitution of 1988 and the Statute of Children and Adolescents. Through bibliographic and jurisprudence research and also the specific legislation it starts analyzing the family, the family power and the right of children and youths to living with both parents. Also brings the conceptualization, identification and consequences of parental alienation, making a distinction with Parental Alienation Syndrome. Finally, brings some comments about the judicial instruments provided in Article 6 of Law 12.318/2010 as a way to combat parental alienation.